Political Realignment in Tokyo: Impact on India-Japan Relations - Arpita Mathur (2016)
India-Japan relations seem to be in a state of uncertainty under the new Hatoyama government. Yet, thanks to many overlapping concerns and opportunities, bilateral ties are likely to progress well. Both sides must reaffirm their commitment to each other soon.